2012
DOI: 10.4103/2277-9175.96067
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transdifferentiation of human adipose-derived stem cells into Schwann-like cells: A promise for treatment of demyelinating diseases

Abstract: Background:Schwann cells (SCs) can provide a suitable option for treatment not only diseases of peripheral nervous system (PNS), but also diseases of central nervous system (CNS). It is difficult to obtain sufficient large number of SCs for clinical purpose because of their restricted mitotic activity, and by sacrificing one or more functioning nerves with the consequence of loss of sensation. So, providing an alternative source for transplantation is desired. The aim of this study was isolation, characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…Gonzalez et al [13] showed that MSCs can express pluripotency-related genes, and even more interesting these MSCs were isolated from adult human testes, which could indicate that these cells and PO-MSCs originate from the same cells in the developmental stage of indifferent gonads. Moreover, there are more and more studies confirming the trans-differentiation potential of MSCs [49][50][51][52][53][54][55] which makes them still more interesting to be applied in regenerative medicine and cellular therapies in the future. In the case of cells cultured in this study, we would particularly suggest using them in the frame of restoring ovarian function in cases of its impairment or of premature ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
“…Gonzalez et al [13] showed that MSCs can express pluripotency-related genes, and even more interesting these MSCs were isolated from adult human testes, which could indicate that these cells and PO-MSCs originate from the same cells in the developmental stage of indifferent gonads. Moreover, there are more and more studies confirming the trans-differentiation potential of MSCs [49][50][51][52][53][54][55] which makes them still more interesting to be applied in regenerative medicine and cellular therapies in the future. In the case of cells cultured in this study, we would particularly suggest using them in the frame of restoring ovarian function in cases of its impairment or of premature ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies demonstrated that ADSCs seems to be one ideal cell source for transdifferentiation into SCs [40]. In our previous study, using a standard protocol, ADSCs were induced into SCs [22].…”
Section: Transdifferentiation Potential Of Adscs Into Schwann Cells Amentioning
confidence: 96%
“…In addition, Kanno et al, in their study concluded that the combination of SC transplants engineered to secrete neurotrophin and chondroitinase further improves axonal regeneration and sensorimotor function [45]. In our previous study, we indicated that ADSC are a good option to induce SCs-like for transplantation in demyelinating disease [22]. Moreover, these cells were able to generate components of myelin shell when exposed to Leukemia inhi-bitory factor (LIF) [24].…”
Section: Transdifferentiation Potential Of Adscs Into Schwann Cells Amentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiated rat [4, 15,16] and also human [17,18] Schwann-like cells expressed in vitro myelin proteins, glial markers, and induced neurite sprouting. Further, coculturing of ASCs with Schwann cells resulted also in differentiation of ASCs into Schwann-like cells [19][20][21].…”
mentioning
confidence: 99%